2017
DOI: 10.1371/journal.pone.0174899
|View full text |Cite
|
Sign up to set email alerts
|

Rapid tissue regeneration induced by intracellular ATP delivery—A preliminary mechanistic study

Abstract: We have reported a new phenomenon in acute wound healing following the use of intracellular ATP delivery—extremely rapid tissue regeneration, which starts less than 24 h after surgery, and is accompanied by massive macrophage trafficking, in situ proliferation, and direct collagen production. This unusual process bypasses the formation of the traditional provisional extracellular matrix and significantly shortens the wound healing process. Although macrophages/monocytes are known to play a critical role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 71 publications
5
25
0
Order By: Relevance
“…endothelial cells during tube formation in vitro [ 15 ] or also during wound healing in experimental animal studies in vivo [ 17 ], is the result of the uptake and subsequent metabolic processing of polyP microparticles. The present study of polyP microparticles and the observed growth of the intracellular ATP pool also impressively confirms a recent study, where ATP (encapsulated into nano-/microparticles) initiated and maintained rapid tissue regeneration [ 18 ].…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…endothelial cells during tube formation in vitro [ 15 ] or also during wound healing in experimental animal studies in vivo [ 17 ], is the result of the uptake and subsequent metabolic processing of polyP microparticles. The present study of polyP microparticles and the observed growth of the intracellular ATP pool also impressively confirms a recent study, where ATP (encapsulated into nano-/microparticles) initiated and maintained rapid tissue regeneration [ 18 ].…”
Section: Introductionsupporting
confidence: 91%
“…These data strongly suggested that not only an intracellular ATP rise but also an exposure to polyP result in an intensified (neo)vascularization. It is a constructive coincidence that almost simultaneously with our report on the acceleration of the wound healing process by application of polyP microparticles [ 17 ] an independent report was published that indicated that such a rapid wound regeneration can also be initiated and completed by encapsulated ATP [ 18 ]. As main causative factors for this rapid tissue regeneration, both macrophage activation and neo-vascularization had been assumed [ 18 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…These concentrations of energy metabolites in the wounds of patients with diabetes were significantly lower than those of normal patients (Smith, Mills et al, 1999). Given that energy is required for every aspect of the wound healing process, many strategies sustain the cellular ATP level by encapsulated ATP or blocked ATP loss would be developed as medications for morphogenetically active wound-healing formulations (Muller, Wang et al, 2017, Sarojini, Billeter et al, 2017.…”
Section: Discussionmentioning
confidence: 99%